Evaluation of physical factor affecting decision for creating the active community centers: the case of Malaysia - Jafari, Nastaran; Utaberta, Nangkula; Mydin, Md Azree Othuman (American-Eurasian Network for Scientific Information, 2016)
Access to the Community center has widely been identified to be one of the most a significant aspect in community design and planning towards better quality living. Although, the Malaysian community centers are not being used effectively and these have been faced with lack of participation. Based on this problem, this study conducted to identify the physical principles for formulating a framework to access the active community center. It was aimed to compare the result of the scientific analysis with the user responses from the community centers’user. For this purpose a questionnaire survey was conducted among four community centers of Kuala Lumpur. In order to evaluate the current condition of Malaysian community center, the questionnaire was prepared based on physical factors. These physical factors contain two main priciples: the first was the accessibilityof the community center and the second was about physical condition of the builing. The results indicate the level of user evaluation in terms of physical factor which are provided in Kuala Lumpur community centers. The approach to investigate the physical factors of community centers in this study can be applied to even different types of public space. The results and improvement suggestions are suitable for other research, for the quality of public space and life in the community center.